Clinical value of weight-bearing CT and radiographs for detecting patellofemoral cartilage visualized by MRI in the MOST study. Issue 11 (November 2021) - Segal, N.A.; Murphy, M.T.; Everist, B.M.; Brown, K.D.; He, J.; Lynch, J.A.; Nevitt, M.C.
Summary: Objective: The patellofemoral joint is frequently affected by osteoarthritis (PFOA) and is incompletely imaged on radiographs (XR). Weight-Bearing CT (WBCT) could offer advantages for visualization. This study determined the sensitivity, specificity, and accuracy of axial WBCT and lateral XR for detection of PFOA features in comparison with cartilage damage on MRI. Design: A convenience sample of 60 right knees from the MOST cohort were analyzed. WBCT and XR were read for OARSI JSN score and MRI for MOAKS cartilage score by two experienced musculoskeletal radiologists blinded to participant. Using MOAKS scoring on MRI (referent standard), the sensitivity, specificity and accuracy of patellofemoral OARSI JSN scores based on WBCT and XR were compared. Results: The mean ± SD age and BMI for the participants included (66.7% women) were 67.6 ± 9.8 years and 30.0 ± 5.3 kg/m 2 respectively. WBCT demonstrated significantly greater sensitivity (0.85–0.97 on WBCT vs 0.47–0.57 on XR) and accuracy (0.85–0.92 on WBCT vs 0.48–0.57 on XR) for all parameters except lateral full-thickness cartilage loss (McNemar's test p -values all <0.001). There was moderate-to-strong and low-to-moderate agreement between PFOA findings on WBCT and XR, respectively, and semi-quantitative scores of PF cartilage on MRI. Inter-rater reliability for XR JSN [weighted kappa = 0.83 (0.64, 1.0)], WBCT JSN [kappa = 0.60 (0.48, 0.72)] and MRI MOAKS-CM [kappa = 0.70 (0.61, 0.79)] readings were good. Conclusion: WBCT demonstrates significantly greater sensitivity and accuracy than radiographs for identification of PFOA. Given the same Relative Radiation Level as XR and improved visualization, WBCT holds promise to improve understanding of the weight-bearing patellofemoral joint.